Housing Policy: The Case of Lublin (Economic and Political Thought, 2024)
The article provides a review of Lublin’s housing policy after 1989. The objective of the article is to assess the conducted housing policy – its nature, directions, principles, and consequences. The analysis focuses on actions carried out by local authorities, as well as programs developed by the government and their impact on housing in Lublin. When describing the specific issues in housing policy, attention is given to the challenges or problems accompanying the introduced changes. Authorities, utilizing various tools, can effectively influence the evolution of housing, concurrently pursuing additional goals. Housing policy may not only affect housing but also serve as a significant element of broader development of the city. Its crucial role will be played by integrating it with other ongoing initiatives or fostering collaboration between authorities and the local community.
Keywords: housing policy, Lublin, city